Implementation of murottal and mujawwad rhythm to improve children's skills in reading al-Qur’an - Solihin, Rahmat; Iqbal, Muhammad; Muin, Muhammad Tamsil (Universitas Muhammadiyah Magelang, 2021)
Reading the Al-Qur’an by enhancing the reading is one of the recommendations in Islam. Therefore, it is necessary to hold activities to introduce the reading of the Al-Quran properly and correctly and in a beautiful voice. One of them is by implementing the murottal and mujawwad rhythms. Community service activities are carried out at the Tahfizh Nurul Qur'an At-Taqwa House, which wass one of the best Al-Quran learning institutions in Tangerang City. The activity began with a prayer and the utterance of a vow. Then proceed with introductions, demonstrations and direct practice of the murottal and mujawwad rhythms. Based on the results of the evaluation, enthusiasm during the activity enabled the participants to recognize and differentiate between murottal and mujawwad. In order to improve these skills, participants need to repeat the material they have learned over and over.